Deep Learning in Physics Education: Exploring the Potential of Mindful, Meaningful, and Joyful for a Better Learning Experience - Sumarni, Ria Asep; Okyranida, Indica Yona (UNIVERSITAS INDRAPRASTA PGRI, 2025)
This article explores the synergistic potential of integrating the Deep Learning approach with the Mindful, Meaningful, and Joyful learning paradigm to enhance physics education. Traditional physics instruction often faces